Neuroimmune Mechanisms in Signaling of Pain During Acute Kidney Injury (AKI) - Gupta, Aprajita; Kumar, Dev; Puri, Sanjeev; Puri, Veena (Frontiers in Medicine, 2020)
Acute kidney injury (AKI) is a significant global health concern. The primary causes of AKI include ischemia, sepsis, and nephrotoxicity. The unraveled interface between the nervous system with the immune response with a specific focus on pain pathways is generating huge interest in reference to AKI. The nervous system through static executes functions by nerve fibers throughout the body. Neuronal peptides released by nerves affect the immune response to mediate the hemodynamic system critical to the functioning of the kidney. Pain is the outcome of cellular cross-talk between nervous and immune systems. The widespread release of neuropeptides, neurotransmitters, and immune cells contribute to bidirectional neuroimmune cross talks for pain manifestation. Recently, we have reported pain pathway genes that may pave the way to better understand such processes during AKI. An auxiliary understanding of the functions and communications in these systems will lead to novel approaches in pain management and treatment through the pathological state, specifically during acute kidney injury.